BIOECOLOGICAL FEATURES OF CISTANCHE MONGOLICA BECK, COMMON IN THE YAZYAVAN STATE NATURAL MONUMENT (Scientific journal of the Fergana State University, 2023)
This article describes the Cistanche mongolica Beck, common in the Yazyavan State Natural Monument, provides information about the bioecological features and significance of the plant. Cistanche mongolica Bess is a perennial parasitic plant of the family Orobanchaceae, adapted to parasitize mainly on the roots of species of the genus Tamarix. This plant is found on sandy saline soils of the Yazyavan State Monument of Nature. It is used in folk medicine, as well as in medicine because of its medicinal properties, so the spread of the plant in this area, the state of its populations, their protection is of great importance.